MOTS-c and Exercise Restore Cardiac Function by Activating of NRG1-ErbB Signaling in Diabetic Rats - Li, Shunchang; Wang, Manda; Ma, Jiacheng; Pang, Xiaoli; Yuan, Jinghan; Pan, Yanrong; Fu, Yu; Laher, Ismail (Frontiers in Endocrinology, 2022)
Pathologic cardiac remodeling and dysfunction are the most common complications of type 2 diabetes. Physical exercise is important in inhibiting myocardial pathologic remodeling and re-storing cardiac function in diabetes. The mitochondrial-derived peptide MOTS-c has exercise-like effects on improving insulin resistance, decreasing the elevated blood glucose, and reducing lipid accumulation. A rat model of type 2 diabetes was induced by feeding a high-fat high-sugar diet combined with an injection of a low-dose of streptozotocin. We investigated the effects and transcriptomic profiling of MOTS-c and aerobic exercise on cardiac properties. Both aerobic exercise and MOTS-c treatment reduced abnormalities in cardiac structure and function. Transcriptomic function enrichment analysis revealed that MOTS-c had exercise-like effects on inflammation, myocardial apoptosis, angiogenesis and endothelial cell proliferation and migration. Moreover, the NRG1-ErbB4 pathway may be important for both MOTS-c and exercise improvements in cardiac dysfunction in diabetes. Our data suggest that MOTS-c activates NRG1-ErbB4 signaling and mimics exercise-induced cardio protection in diabetes.